Reflection of the Religious Situation in the World View of Russian Native Speakers - Kravcova, Liudmila (Respectus Philologicus, 2012)
The article documents the changing perceptions of the global religious landscape among Russian native speakers by analysing changes in the number of Russian nouns denoting the religious affiliation of the people they refer to. The research is based on the comparison of the Explanatory Dictionary of the Russian Language of the Early 21st Century – Contemporary Vocabulary, edited by G. N. Sklyarevskaya, and Ozhegov’s Dictionary, one of the most popular dictionaries of the Soviet period. The article also suggests reasons for the absence of certain lexicons in the dictionary of the Soviet era. Words denoting practitioners of Islam are one of the main focal points of this study. The ascending role of Islam in global politics, and the increasing attention paid to schisms within this religion, have created a demand for precise definitions of the various concepts of Islam. To capture this linguistic development, we have analysed the relationships and semantic connections among the words мусульманин, правоверный, исламист, ваххабит, шахид, and other words whose meanings contain an Islamic component. We conclude that dictionaries tend to capture the everyday meanings of words, which are often a product of only a superficial grasp of the underly ing concept and commonly formed on the basis of mass media discourse, which, in turn, is subject to uncertainties of meaning. The limited set of contextual components attached to words denoting religious concepts speaks to the fact that the understanding of the current religious situation and its ongoing developments is rather vague among Russian native speakers.